Promoting SDG 15: Life on Land Development of Socioscientific Issue-Based E-Module on Gold Mining in ESD to Facilitate Students Critical Thinking Skill and Anticipatory Competency - Umar, Mohammad Farhan; Riandi*, Riandi; Solihat, Rini; Yunus, Sitti Rahma (Universitas Syiah Kuala, 2025)
Indonesia, with its abundant natural resources, needs to implement wise and sustainable management it line with SDG 15 to maintain ecosystem balance and support life. Education plays a crucial role in achieving sustainable development. An e-module was developed as an educational initiative to promote SDG 15 by integrating socios-scientific issues (SSI) related to gold mining, aiming to facilitate critical thinking skills (CTS) and anticipatory competency (AC). This study aims to develop and evaluate the e-module product. The research method employed is research and development (Rd) using ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. However, the implementation stage was not applied in this study. Data collection utilized e-module validation sheets as instruments. The research subjects consisted of experts validators, including 2 biology education lecturers and 2 professional biology science teachers. The results show that the validation scores from experts were as follows: material aspect with an average score of 3.71 (highly valid), content presentation aspect with an average of 3.72 (highly valid), linguistic aspect with an average of 3.77 (highly valid), and graphic design aspect with an average of 3.79 (highly valid). Overall, the developed e-mode is valid for use, though further research is still required to test its effectiveness.